Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Biomass-derived ceramic packing coupled with an Fe–Mn modified graphite felt cathode for enhanced bioelectro-Fenton/biotrickling filtration of gas-phase styrene - Shu-Hui Liu; Yu-Sheng Yang; Chi-Wen Lin; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Zinc-binding protein metallothionein 3 protects vascular smooth muscle cells from ferroptosis via blocking lysosomal degradation of GPX4 - Wenxin Lin; Xin Feng; Jingjie Chen; Bo Huo; Xian Guo; Molin Yang; Ding-Sheng Jiang; Linling Yu; Yue Chen (Journal of Molecular Medicine, 2026)

Correction: Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Detecting hidden ping-pong records in mobile phone location data by considering daily activity patterns - Zhiyuan Zhao; Qinyi Lin; Wenting Zhang; Zhixiang Fang; Xiping Yang; Sheng Wu (Travel Behaviour and Society, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Depth-dependent regulation of soil desiccation cracking by geotextiles - Peiyuan Lin; Xun Yuan; Yang Chen; Sheng Li (Geotextiles and Geomembranes, 2026)

A novel benefit-oriented multi-objective optimization framework for efficiency, NOx, and H2S in coal-fired boilers - Cong Wang; Yiqing Yang; Bowen Lin; Jiaqi Ma; Jun Xu; Kai Xu; Long Jiang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Deep eutectic solvent plasticization of chitosan/distiller's grains prolamin films: Hydrogen bond-driven structural regulation and enhanced food preservation performance - Lin Deng; Haoyang Sun; Xiaomeng Li; Yi Sun; Yarong Wang; Hongyu Yang; Jian Su; Long Sheng; Jia Zheng; Zhaoxia Cai (Food Research International, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Triple-phase Interface-induced triboelectric-liquid capacitance coupling: Unlocking high power direct-current triboelectric nanogenerators - Xin-Long Xiao; Jiang-Tao Guo; Sheng-Jie Lin; Wen Yang; Yun-Bo Zhang; Yong Zhang; Pei-Zhi Yang (Chemical Engineering Journal, 2026)

In-situ interfacial C–S–Zn bonding in N/S co-doped hard carbon anchoring ZnS for durable and fast sodium storage - Lingling Liu; Chuanyue Yang; Tong Wang; Jingwen Sun; Xu Yao; Ning Sheng; Xiansen Tao; Lin Shi; Jingquan Sha (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Efficiently photocatalytic synthesis of a special dye intermediate with CO2 for preparing a disperse dye SCFM-ANCY suitable for supercritical coloration of bio-based fibers - Yang-Sheng Zhou; An-Tong Liu; Yi-Wei Shi; Lin Xie; Jia-Jie Long (Process Safety and Environmental Protection, 2026)

Glucose-derived carbon-confined cu nanoparticles for selective nitrate reduction to ammonia under acidic conditions and biofouling-resistant wastewater treatment - Tsung-Ying Yang; Ko-Shan Ho; Kan-Yen Hsieh; Yu-Lin Hsiao; Sheng-Ci Jhong; Hsiu-Chung Tu (Journal of Water Process Engineering, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Evaluation of the impact of deltamethrin, dapagliflozin, and KB-R7943 on INa in HL-1 atrial myocytes and U2OS osteosarcoma cells: An investigative study - Sheng-Che Lin; Yang-Kao Wang; Sheng-Nan Wu; Edmund Cheung So (Environmental Toxicology and Pharmacology, 2026)

Self-powered trickling-filter bioelectro-Fenton removal of gaseous isopropanol using sulfur-modified Fe-biochar fillers and a melanin-modified cathode - Chi-Wen Lin; Yu-Sheng Yang; Shu-Hui Liu; Wei Tong Chen; Xiang-En Ke (Chemical Engineering Journal, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Stakeholder priorities dominate the evaluation of climate change impacts on ecosystem-service multifunctionality - Xin Jing; Hao Wang; Wei Xu; Xiaomin Fan; Lin Jiang; Yu Li; Zhiyuan Ma; Peter Manning; Nathan J. Sanders; Bernhard Schmid; Yunfeng Yang; Zhenhua Zhang; et al. (Science China Life Sciences, 2026)

Tea proteins, peptides, and amino acids: A whole-chain review of profile, functionalization, transformation, and valorisation - Zi-Hao Qiu; Qiu-Sheng Zhong; Gao-Zhong Yang; Yin Zhu; Yue Zhang; Qun-Hua Peng; Susanne Baldermann; Zhi Lin; Hai-Peng Lv; Jiang Shi (Trends in Food Science & Technology, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

A two-layer safe reinforcement learning framework for multi-constraint reservoir operation: Integrating action masking and lagrangian dual method - Zaichao Xie; Xiaoli Zhang; Wei Xu; Guoguo Lin; Dong Li; Shuncai Zhang; Hongyan Chen; Sheng Yang (Journal of Hydrology, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

Dynamic interfacial polarization via electric double layer coupling in semiconductor–liquid–metal junctions for direct-current tribovoltaic nanogenerators - Sheng-Jie Lin; Jiang-Tao Guo; Xin-Long Xiao; Wen Yang; Yun-Bo Zhang; Yong Zhang; Pei-Zhi Yang (Chemical Engineering Journal, 2026)

TRIM9-Mediated Degradation of SMAD4 Promotes Pyroptosis and Disruption of the Endothelial Barrier in Aortic Dissection Disease - Hong-Qin Bi; Tan Yang; Sheng-Lin Ling; Feng-Xu Yu (Cardiovascular Toxicology, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Drying induces Mars intermediate-sized cracks: New evidence and insight from geometrical quantification - Jin-Jian Xu; Hao Zhang; Chao-Sheng Tang; Yaowen Yang; Mohamed Ramy El-Maarry; Lin Li; Bin Shi (Icarus, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Quantitative Early Warning of Floor Water Inrush Based on Deep Learning: Joint Response of Microseismic Three-Dimensional Kernel Density and Hydrodynamics - Hang Li; Xianjie Hao; Jinyi Ji; Huaixiang Yang; Wantong Lin; Sheng Zhang; Xinlei Cui (Rock Mechanics and Rock Engineering, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Eremophilane-type sesquiterpenes from Ligularia hodgsonii: isolation, structural characterization, and pro-angiogenic potential - Zhenhua Wan; Huilin Peng; Chunping Tang; Jiangjiang Qin; Bintao Hu; Changqiang Ke; Sheng Yao; Ligen Lin; Yang Ye (Phytochemistry, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

A data-driven comparative risk assessment of marine traffic accidents using an object-oriented Bayesian network - Xue Yang; Zhiying Lin; Wenjun Zhang; Sheng Xu; Shenping Hu (Ocean Engineering, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Fouling behavior and cleaning strategy during treatment of practical refractory organic wastewater using anaerobic ceramic membrane bioreactor - Ruihui Chen; Lixiu Shi; Xinsen Li; Hongming Yang; Sheng Xiang; Mohd Fadhil MD Din; Eli Hendrik Sanjaya; Lu Peng; Zhengwang Wu; Chengcheng Lin; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

Lactate-driven histone lactylation enhances GDF15 secretion in skeletal muscle under mtDNA mutation-induced mitochondrial stress - Yan Lin; Busu Li; Jiayin Wang; Weiyue Si; Xingyu Zhuang; Ying Zhao; Wei Jiang; Wei Wang; Dongdong Wang; Fuchen Liu; Ruonan Duan; Yuying Zhao; et al. (Science Bulletin, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Distinction in Symbiodiniaceae and Bacterial Communities and Symbiodiniaceae Lineage‐Specific Transcriptome Underpinning the Superior Heat Tolerance of Intertidal Acropora Corals - Pan Zhang; Lin‐Tao Huang; Xiao‐Lei Yu; Yu‐Yang Zhang; Sheng Liu; Lei Jiang; Hui Huang (Molecular Ecology, 2026)
Fine‐scale thermal heterogeneity within intertidal and subtidal microhabitats could drive divergence in organismal heat tolerance. Reef corals from the extreme intertidal may hold optimism for the future of coral reefs and give insights into the mechanisms by which coral may persist under future conditions. Here, we compared the thermal sensitivities of intertidal and subtidal Acropora digitifera and evaluated their bleaching phenotypes, transcriptomes, host genetic differentiation and bacterial communities. Results showed that only heat‐exposed subtidal corals displayed significantly reduced photochemical efficiency, symbiont densities, pigment and host protein concentrations, suggesting bleaching and host starvation. Despite being genetically similar, heat‐exposed subtidal corals mounted stronger immune activation and amino acid degradation but downregulated monocarboxylate transport and calcification compared to intertidal corals. In contrast to the prevalence of Cladocopium in subtidal corals, intertidal corals were dominated by Durusdinium , whose transcriptional signature was characterised by lineage‐specific and constitutively high transcript abundance of orthologs involved in stress response, metabolism, photosynthesis, cell cycle and symbiotic interactions. Furthermore, 16S rRNA sequencing demonstrated an origin‐dependent bacterial composition, with Endozoicomonas being more abundant and important in co‐occurrence networks of intertidal corals. Our findings suggest that distinction in Symbiodiniaceae and bacterial communities and Symbiodiniaceae lineage‐specific transcriptional footprint largely underpin the exceptional thermotolerance of intertidal Acropora . Although these corals provide promising avenues for restoration, such a mechanism may bring attention to the risk of using them in selective breeding, particularly given the horizontal transmission of algal symbionts in Acropora .

Phylogeographic Pattern and Genetic Structure of the Cyprinid Fish Microphysogobio kachekensis (Oshima 1926) in Mainland China and Hainan Island Based on Mitochondrial and Nuclear DNA - Jin-Quan Yang; Jiabo Chen; Junjie Wang; Tian-Qi Zhou; Yuh-Wen Chiu; Hung-Du Lin; Wen-Sheng Ou (Fishes, 2026)
South China’s freshwater biodiversity has been shaped by Quaternary climatic oscillations and persistent geological barriers. We investigated the phylogeography and conservation implications of the primary freshwater fish Microphysogobio kachekensis across mainland China and Hainan Island using mitochondrial (cyt b and control region) and nuclear (RAG2 and rpS7-1) markers from 200 individuals. Mitochondrial analyses recovered two major lineages and multiple sublineages largely structured by drainage basins, whereas nuclear data resolved four geographically concordant lineages. Population differentiation was strong (high FST), and SAMOVA/AMOVA supported major barriers restricting gene flow, including the Qiongzhou Strait, Gulf of Tonkin, Yunkai Mountains, and Nanling Mountains. Ancestral-area reconstruction inferred the Pearl River region as the most likely source area, followed by dispersal to northern Hainan and subsequent expansion to southern Hainan and the Red River, with additional northward expansion to the Zhejiang–Fujian region. Despite high haplotype diversity, within-population nucleotide diversity was low, consistent with long-term river isolation and complex demographic history. We propose six ESUs and four MUs for evolutionarily informed conservation and to guide stock enhancement in southern China.

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Insights into the binding mechanism of Monascus pigment with Holo-ovotransferrin by multispectral and molecular dynamics simulation - Yan Fan; Xi-Yuan Guan; Can-Huan Liang; Jia-Lin Chen; Si-Ran Zhang; Sheng Huang; Qin Wang; Wen-Hua Yang (Food Chemistry, 2026)

Feasibility of a Multi-Laboratory Model of Middle Cerebral Artery Thromboembolic Stroke with Thrombolysis: TE-MCAo - Michelle Lin; Mozammel Bhuiyan; Carly McCurry; Jessica Lamb; Marcio A. Diniz; Karni Bedirian; Anil K. Chauhan; Abhishek Jha; Aditi Jain; Enrique C. Leira; Rakeshkumar Patel; Mohammad B. Khan; et al. (Translational Stroke Research, 2026)
No single animal stroke model satisfies all needs of translational stroke investigation. While the nylon filament model is widely accepted in preclinical translational stroke research, thromboembolic models have more physiological relevance. Thromboembolic models are technically difficult, time consuming, and show variable results, making them problematic for multi-laboratory preclinical network use. We sought to develop and validate a multi-laboratory thromboembolic middle cerebral artery occlusion model that encompasses vessel occlusion and subsequent thrombolysis. To reduce the numbers of donor animals used, we developed a method to store donor blood for later use. Using prefabricated microcatheters, we simplified thrombus preparation and handling. Emboli were prepared in microcatheters and injected directly into the middle cerebral artery from the internal carotid artery. For thrombolysis we used intravenous Tenecteplase dosing at 1.5 mg/kg. To demonstrate feasibility and ease-of-use, the model was implemented at six research laboratories. We wrote and field-tested standard operating procedures, training videos, and hands-on surgical training workshops. We enrolled 170 Sprague Dawley rats of both sexes at six laboratories who performed 4 to 6 thrombus embolizations per week. All sites could achieve reproducible occlusion and thrombolysis. Thromboemboli prepared from stored blood served as well as emboli from freshly drawn blood. Of 135 rats who received one embolus, 33 (24%) died before 48-hour MRI scan. In survivors, stroke volume was 13 ± 16% of the ipsilateral hemisphere. Occlusions were seen in the MCA in 15%, distal ICA in 19%, both (T-occlusions) in 2% and in the MCA/ACA in 1%. Corner test, neurobehavioral battery, and MRI showed reasonably consistent stroke injury. We established the feasibility and reproducibility of a multi-laboratory rodent thromboembolic model but further development is needed to improve the success rate and lower the mortality rate before this model can be accepted widely.

Implementation of a Deep Learning Ensemble Framework Based on Bidirectional Message Queues - Xin-Jian Wei; Wu-Yang Yang; Xin Xu; Hai-Shan Li; Nan Wang; Wei-Sheng Wang; Han-Wei Lin; Chen Wang (Applied Geophysics, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Transcriptome-wide identification of glycoRNAs by Clier-seq pipeline - Nannan Zhu; Yan-Lin Yang; Yuan-Tao Liu; Zheng-Zhou Lu; Yan Wang; Yi-Ling Luo; Ning Meng; Yan Yuan; Qian Zhong; Mu-Sheng Zeng (Science China Life Sciences, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Physical model tests under towing conditions of a novel floating wind-wave integrated platform - Zhenpeng Wang; Xiaolong Dai; Songwei Sheng; Yaqun Zhang; Min Chen; Xinhui Chen; Shanxun Yang; Zhaoji Lin (Ocean Engineering, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Sacrificial bond-enabled mechanically robust, stretchable ionic hydrogels for high-performance wearable sensors - Sheng-Lin Qiao; Xiao-Chun Yang; Xiao-Xue Wang; Shou-Shan Yu; Xue-Gang Yu; Ke-Zheng Chen (Chemical Engineering Journal, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

A new perspective on endometriosis: Integrating eQTL mendelian randomization with transcriptomics and single-cell data analyses - Sheng Dou; Yi Wei; Zongyun Lin; Hui Wu; Fenglian Yang; Xuechang Cen; Wenjing Lu; Haimei Qin; Rong Wang; Junli Wang (Functional & Integrative Genomics, 2025)
Endometriosis is caused by the migration of endometrial cells to locations outside the uterine lining. Despite the increasing prevalence of endometriosis, there has been limited research on genetic effects, and its molecular mechanisms remain unclear. This study aimed to investigate the mechanisms underlying the development of endometriosis and to identify new genetic targets for endometriosis by integrating data from gene chips, single-cell mapping, and genome-wide association study databases. Using the Gene Expression Omnibus database, we downloaded data on normal endometrium, eutopic endometrium, and ectopic lesion tissues to explore the differentially expressed genes (DEGs) between normal and eutopic endometrium, and between eutopic and ectopic endometrium. Assessment of the relationships between DEGs and endometriosis involved differential expression, expression quantitative trait loci (eQTL), and Mendelian randomization (MR) analyses. Two single-cell atlas datasets were then analyzed to explore the mechanisms underlying disease development and progression. Intersection of MR results with DEGs between normal and eutopic endometrium highlighted 28 candidate biomarker genes (17 upregulated and 11 downregulated). Similarly, we identified two additional candidate biomarker genes by intersecting the DEGs between eutopic and ectopic endometrium with MR results. Among these 30 candidates, further filtering using single-cell datasets revealed that the histamine N-methyltransferase ( HNMT ), coiled-coil domain containing 28 A ( CCDC28A ), fatty acid desaturase 1 ( FADS1 ) and mahogunin ring finger 1 ( MGRN1 ) genes were differentially expressed between the normal and eutopic groups, consistent with transcriptomic and MR results. Our findings suggested that eutopic endometrium exhibits epithelial-mesenchymal transition (EMT). Cell communication analysis focused on ciliated epithelial cells expressing CDH1 and KRT23 revealed that, in the eutopic endometrium, ciliated epithelial cells are strongly correlated and interact with natural killer cells, T cells, and B cells. We identified four novel biomarker genes and found evidence for EMT in the eutopic endometrium. The mechanism of endometriosis progression may be closely related to EMT and changes in the immune microenvironment triggered by damage to ciliated epithelial cells.

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Influence of Pearl river plume and coastal upwelling on planktonic foraminiferal assemblages in the northern South China Sea - Rick J. Yang; Hui-Ling Lin; Tai-Chun Lin; Jay Lee; James T. Liu; Horng-Sheng Mii (Marine Environmental Research, 2025)

Enhanced insecticidal activity and bioavailability of thiacloprid from pH-responsive porous MPN(Fe)@ZIF-8 nanocarrier - Miao Wang; Donghui Xu; Ying Zhang; Jie Zhou; Zhihao Lin; Yiming Zhao; Xin Ding; Bin Sheng; Xiaobin Wen; Xiao Song; Ge Chen; Xiaomin Xu; et al. (Journal of Cleaner Production, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

A long-term common garden experiment reveals geocytotype-dependent succession of plant community invaded by Solidago canadensis - Dongyan Feng; Jiliang Cheng; Zhongsai Tian; Xianghong Yang; Lei Lin; Huan Zhang; Zhen Wang; Sheng Qiang (Journal of Plant Research, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Effects of U stress on physiological tolerance characteristics and mineral element distribution of sunflower seedlings - Ming-Ying Zeng; Yuan-Lin Yang; Sheng Zheng (Journal of Environmental Radioactivity, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Does the gall-forming cecidomyiid enhance host plant leaves and their phytochemicals? A case study of Bruggmanniella litseae (Diptera: Cecidomyiidae) - Charles Ko-Hsuan Wang; Sheng-Feng Lin; Hieng-Ming Ting; Man-Miao Yang; Meng-Yuan Huang (Arthropod-Plant Interactions, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Ceramifiable flame-retardant silicone rubber foam for long-term fire resistance and thermal insulating - Tao Lin; Ke Shang; Gui-De Lin; Jun-Sheng Wang; Jin-Jun Yang (Chemical Engineering Journal, 2025)

Multiscale structural design of heterostructured carbon/boron nitride aerogels for efficient thermal conductivity and broadband electromagnetic wave absorption - Zhengxuan Li; Wang Yang; Chen Zhang; Zhongzhen Ding; Shaoxiong Du; Xi Wu; Junyan Dong; Wenjie Zhu; Sheng Liu; Yu Lin; Lei Liu; Yongfeng Li (Chemical Engineering Journal, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Multi-chamber bipolar membrane electrodialysis for high-purity lithium hydroxide production: A case study - Qiuyue Wang; Sheng He; Minghong Li; Benxian Yang; Lin Tian; Nicholas Ze-Xian Low (Journal of Water Process Engineering, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Single-cell sequencing and spatial transcriptomics reveal FAS+ T cell and autophagy-related signatures predicting chemoimmunotherapy response in diffuse large B-cell lymphoma patients - Ning Lou; Liyuan Dai; Ruyun Gao; Jianliang Yang; Lin Gui; Sheng Yang; Peng Liu; Yuankai Shi; Xiaohong Han (Science China Life Sciences, 2025)

Exploration of complex physical and chemical processes of a severe haze episode over central Taiwan - Chuan-Yao Lin; Wen-Mei Chen; Yang-Fan Sheng; Wan-Chin Chen; Hing Cho Cheung; Charles; C.K. Chou (Science of The Total Environment, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Association of prenatal exposure to perfluoroalkyl and polyfluoroalkyl substances with fetal growth trajectories - Yi Yang; Sheng Teng; Leshi Lin; Wenjuan Li; Zhenzhen Zhu; Tangxin Chen; Li Li; Fang Peng; Dongmei Peng; Xiao Gao (Environmental Research, 2025)

Optimizing pyrolysis of herbal tea and Salvia miltiorrhiza residues for sustainable energy and product recovery - Yan Chen; Jingyong Liu; Liangzhong Li; Xin Chen; Ziting Lin; Chunxiao Yang; Fatih Evrendilek; Weixin Li; Wenxiao Huang; Yao He; Sheng Zhong; Zuoyi Yang (Chemical Engineering Journal, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of neonicotinoid pesticide exposure in the first trimester on gestational diabetes mellitus based on interpretable machine learning - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Yonghong Sheng; Yang Xu; Dongping Huang; Shun Liu; Xiaoyun Zeng; Virasakdi Chongsuvivatwong; Xiaoqiang Qiu (Environmental Research, 2025)

Antibacterial antioxidant polyurethane/curcumin patch with anti-swelling ability for tissue adhesion and treatment of oral ulcers - Xiaolei Guo; Lin Yang; Nan Sheng; Xirui Long; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Modeling and optimization of docosahexaenoic acid production by Schizochytrium sp. based on kinetic modeling and genetic algorithm optimized artificial neural network - Zi-Lei Chen; Hui Lian; Lin-Hui Yang; Yang Wu; Bo Ren; Dong-Sheng Guo (Bioresource Technology, 2025)

Effective Strategies for Accelerating the Phase-Out of Mercury Thermometers in Underdeveloped Regions: A Critical Step Towards Implementing the Minamata Convention on Mercury - Wanying Lin; Qihong Yang; Zhanhua Zhang; Xia Sheng; Tong Zhang; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Mesenchymal stem cell-derived exosomes carry miR-125a-5p to improve diabetic keratopathy by regulating endoplasmic reticulum stress - Weina Li; Shiping He; Chaoqun Lin; Sheng Yang; Wenbin Zhang (Tissue and Cell, 2025)

Mechanistic and kinetic understanding of Pb-phosphate biomineralization from humic acid-bound Pb under active growth of phosphate solubilizing Enterobacter aerogenes W6 - Zhihui Yang; Lin Yu; Xiao Yan; Penggang Li; Mengying Si; Qi Liao; Feiping Zhao; Zhang Lin; Anxu Sheng; Weichun Yang (Journal of Environmental Management, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Research on arch dam deformation prediction method based on interpretability clustering and panel data model - Dongyan Jia; Jie Yang; Chunhui Ma; Lin Cheng; Sheng Xiao; Xiuxiu Gong (Engineering Structures, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Bimetallic active sites with tailored d-bands boost multistep sulfur redox reactions for enhanced lithium-sulfur battery performance - Wei Wang; Jianguo Si; Liguo Yue; Weicai Zhang; Qingqing Chen; Haoliang Huang; Fei Lin; Yang Zhao; Sheng Meng; Lifeng Liu (Chemical Engineering Journal, 2025)

Novel cell factory for the production of 24-epi-ergosterol, an un-natural semi-synthetic precursor for the production of brassinolide in Yarrowia lipolytica - Yuanying Wang; Shuxian Liu; Zeyu Sheng; Yun Feng; Yinmiao Wang; Yiqi Jiang; Li Zhu; Mianbin Wu; Lirong Yang; Jianping Lin (World Journal of Microbiology and Biotechnology, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Efficiently radiation-induced degradation and extraction of Polygonatum sibiricum polysaccharides and its excellent ROS scavenging properties - Dong-Xu Tang; Shi-Zhong Zhou; Zhi-Jun Wang; Yang-Lin Zhang; Kun Liu; Jin-Yu Yang; Xiao-Jie Yang; Yue-Sheng Li; Xia Zhang (Chemical Engineering Journal, 2025)

Synthetic biology meets Aspergillus: engineering strategies for next-generation organic acid production - Yang Wu; Qian-Hui Xu; Zi-Lei Chen; Lin-Hui Yang; Dong-Sheng Guo (World Journal of Microbiology and Biotechnology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

A New Rock Damage Constitutive Model Based on Usher Function and its Application to Brittleness Evaluation - Yun-peng Guo; Dong-qiao Liu; Sheng-kai Yang; Yang Wang; Yi Hu; Xiao-peng Zhang; Jie-yu Li; Yan-peng Lin; Zhong-wei Li (Rock Mechanics and Rock Engineering, 2025)

Additional benefits of combined ceftriaxone and adipose-derived mesenchymal stem cells on revamping the outcomes in rodent after acute spinal infection - Tsung-Cheng Yin; Hung-Sheng Lin; Pei-Hsun Sung; John Y. Chiang; Chien-Hui Yang; Hon-Kan Yip; Kuan-Hung Chen (Journal of Molecular Histology, 2025)

Decreased net N nitrification rate constrains soil N availability during long-term Camellia oleifera cultivation - Tinghao Zong; Jingwei Ma; Xinming Guan; Yusong Lin; Yuqi Chen; Meiqi Wang; Jiaze Lv; Yichao Rui; Yang Chen; Lichao Wu; Sheng Lu (Applied Soil Ecology, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

A crazy trio in Parkinson's disease: metabolism alteration, α-synuclein aggregation, and oxidative stress - Sheng Li; Yanbing Liu; Sen Lu; Jiayi Xu; Xiaokun Liu; Di Yang; Yuxuan Yang; Lin Hou; Ning Li (Molecular and Cellular Biochemistry, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Electrochemical removal of hydrogen sulfide and recovery of the deposited sulfur on the anode from wastewater - Riying Qi; Yanqiu Yang; Kuichuan Sheng; Hongjian Lin (Journal of Environmental Chemical Engineering, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

A new method to estimate the soil freezing characteristic curve - Jun Bi; Chaozheng Shen; Guoxu Wang; Zhijian Wu; Sheng Yang; Jianguo Lu; Gaochao Lin (Cold Regions Science and Technology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Quantify the effects of water-soluble salts and available fractions of nutrient elements on mobility of cadmium in paddy soil: A case study of the Pearl River Delta - Changchen Huang; Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Yuanhang You; Kun Lin; Cheng Li (Journal of Cleaner Production, 2024)

Janus-Adhesive ionogels for wearable Real-Time monitoring and prevention of infantile meningitis - Xiao-Chun Yang; Xiao-Xue Wang; Chen-Yu Wang; Meng Yin; Ke Ma; Yan Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Composition modulation of electrocatalysts based on 3d transition metal towards high-performance Zn-air batteries - Ya-Fei Guo; Xu Liu; Shao-Jie Yang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Chun-Sheng Li; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Synergistic Triple-Action morphological composite Anode: Integrating lattice Softening, Interfacial electric Fields, and dual confinement for superior Potassium-Ion battery performance - Jia-Sheng Lin; Yi-Yen Hsieh; Kai-Yuan Hsiao; Yi-Chun Yang; Che-Hung Wang; Ming-Yen Lu; Wen-Wei Wu; Hsing-Yu Tuan (Chemical Engineering Journal, 2024)

Transcriptome analysis of Sesuvium portulacastrum L. uncovers key genes and pathways involved in root formation in response to low-temperature stress - Jingyi Yang; Shiyu Lin; Yinghan Shen; Jingtao Ye; Xiamin Jiang; Sheng Li; Maowang Jiang (Plant Molecular Biology, 2024)

Local adaptation of trophic strategy determined the tolerance of coral Galaxea fascicularis to environmental fluctuations - Xiao-Lei Yu; Cheng-Yue Liu; Lei Jiang; Lin-Tao Huang; Yong Luo; Pan Zhang; Yu-Yang Zhang; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Expressional respones of hsp70 genes against abiotic and entomopathgenic stresses in four different noctuid larval species (Lepidoptera: Noctidae) - Yu-Ting Shi; Zheng Zhai; Zi-Yao Liu; Le Zhou; Hua Yang; Lin Chen; Yong-Sheng Zhang; Huan Yu (Pesticide Biochemistry and Physiology, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Identification and health risk assessment of volatile and semi-volatile migrants along with chemical elements in food contact water-borne coating paper - Qing-Hua Yang; Qin-Bao Lin; Xin-Yu Hua; Jia Liao; Shi-Qiang Lu; Ling-Yan Yan; Hong-Sheng Ma (Food Packaging and Shelf Life, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Interlayer cross-linked MXene enables ultra-stable printed paper-based flexible sensor for real-time humidity monitoring - Hao-wen Zhang; Xiang Xu; Meng-lin Huang; Yang-sheng Wang; Zhao-quan Xu; Zhe-sheng Feng; Yagang Zhang; Yan Wang (Chemical Engineering Journal, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

Lead-rivet strategy of growing perovskite nanocrystals for excellent toxicity inhibition and spinning application - Hanlong Wang; Shifeng Zhu; Jiaoyue Sheng; Feihong Gao; Lei Yang; Xili Hu; Francisco Fernández-Martínez; Longhui Lin; Chaoyu You; Dongming Xing (Journal of Hazardous Materials, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Novel GaN-Based Substrates with Gold Nanostructures for Ultra-Sensitive SERS Analysis: Micro-Nano Pit Morphology for Enhanced Molecular Detection - Tsung-Shine Ko; Chen-An Deng; Jiann Shieh; Hung Ji Huang; Yung-Sheng Lin; Yang-Wei Lin; Yi-Chun Du (Journal of Medical and Biological Engineering, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Physicochemical, thermodynamic, and kinetic controls on volatile products, bio-oils, and biochars of Lycium barbarum pyrolysis and their multi-objective optimization - Siqi Chen; Sen Lin; Shengzheng Huang; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Yao He; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Jingyong Liu (Fuel, 2024)

Effect of succinylation-assisted glycosylation on the structural characteristics, emulsifying, and gel properties of walnut glutenin - Yuanli Wang; Liang Tao; Zilin Wang; Yue Wang; Xinyue Lin; Jiahe Dai; Chongying Shi; Tianyi Dai; Jun Sheng; Yang Tian (Food Chemistry, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Loss-of-function mutation in DDX53 associated with hereditary spastic paraplegia-like disorder - Xiangshu Yuan; Ya Wang; Xiyuan Li; Sheng Zhong; Danyi Zhou; Xianlong Lin; Hezhi Fang; Yanling Yang; Maofeng Wang (Journal of Molecular Medicine, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Analytical model for prestressed glulam beams reinforced with unbonded steel bars - Lidan Mei; Jing Ren; Xueyan Lin; Mingtao Wu; Nan Guo; Wenbin Yang; Ye Sheng (Engineering Structures, 2024)

Influence of desiccation during freeze-thaw cycles on volumetric shrinkage and tensile strength of compacted clayey soils - Yao Wei; Chao-Sheng Tang; Cheng Zhu; Qing Cheng; Yang Lu; Lin Li; Ben-Gang Tian; Bin Shi (Engineering Geology, 2024)

Second-generation bioenergy to decouple fossil fuel dependency and environmental deterioration: Dynamic and optimal mechanisms and gas-to-ash products of combustion of Pennisetum hydridum - Sen Lin; Li Wang; Jingyong Liu; Zebin Wei; Fatih Evrendilek; Jiayu Liang; Ziting Lin; Zuoyi Yang; Sheng Zhong (Biomass and Bioenergy, 2024)

Electroacupuncture Exerts Analgesic Effects by Restoring Hyperactivity via Cannabinoid Type 1 Receptors in the Anterior Cingulate Cortex in Chronic Inflammatory Pain - Junshang Wu; Libo Hua; Wenhao Liu; Xiaoyun Yang; Xiaorong Tang; Si Yuan; Sheng Zhou; Qiuping Ye; Shuai Cui; Zhennan Wu; Lanfeng Lai; Chunzhi Tang; et al. (Molecular Neurobiology, 2024)
As one of the commonly used therapies for pain-related diseases in clinical practice, electroacupuncture (EA) has been proven to be effective. In chronic pain, neurons in the anterior cingulate cortex (ACC) have been reported to be hyperactive, while the mechanism by which cannabinoid type 1 receptors (CB1Rs) in the ACC are involved in EA-mediated analgesic mechanisms remains to be elucidated. In this study, we investigated the potential central mechanism of EA analgesia. A combination of techniques was used to detect the expression and function of CB1R, including quantitative real-time PCR (q-PCR), western blot (WB), immunofluorescence (IF), enzyme-linked immunosorbent assay (ELISA), and in vivo multichannel optical fibre recording, and neuronal activity was examined by in vivo two-photon imaging and in vivo electrophysiological recording. We found that the hyperactivity of pyramidal neurons in the ACC during chronic inflammatory pain is associated with impairment of the endocannabinoid system. EA at the Zusanli acupoint (ST36) can reduce the hyperactivity of pyramidal neurons and exert analgesic effects by increasing the endocannabinoid ligands anandamide (AEA), 2-arachidonoylglycerol (2-AG) and CB1R. More importantly, CB1R in the ACC is one of the necessary conditions for the EA-mediated analgesia effect, which may be related to the negative regulation of the N-methyl-D-aspartate receptor (NMDAR) by the activation of CB1R downregulating NR1 subunits of NMDAR (NR1) via histidine triad nucleotide-binding protein 1 (HINT1). Our study suggested that the endocannabinoid system in the ACC plays an important role in acupuncture analgesia and provides evidence for a central mechanism of EA-mediated analgesia.

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

Cytotoxic flavonoids from the leaves of Callicarpa nudiflora hook - Jin-Lin Zhang; Yin Xiao; Lu Zhou; Shao-Yang Yin; Jia-Yin Long; Hong-Lin Xiang; Xi-Feng Sheng; Hui Zou (Natural Product Research, 2024)

Experimental investigation on the influence of NaCl concentration on triaxial mechanical behaviors of a low-clay shale - Sheng-Qi Yang; Wang-Xing Hong; Jian-Guo Wang; P.G. Ranjith; Xiao-Lin Wang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Evaporation and desiccation cracking of soils: Experiment evidence and insight on the freeze-thaw cycle dependence - Yao Wei; Chao-Sheng Tang; Yang Lu; Mingli Zhang; Qing Cheng; Lin Li; Bin Shi (Engineering Geology, 2024)

An implicit stabilized material point method for modelling coupled hydromechanical problems in two-phase geomaterials - Qin-yang Sang; Yong-lin Xiong; Rong-yue Zheng; Xiao-hua Bao; Guan-lin Ye; Sheng Zhang (Computers and Geotechnics, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Quantifying the effects of viral load on multistate COVID-19 infection and the progression of the Alpha and Omicron VOCs: a Bayesian competing Markov exponential regression model - Yen-Po Yeh; Amy Ming-Fang Yen; Ting-Yu Lin; Chen-Yang Hsu; Sam Li-Sheng Chen; Tony Hsiu-Hsi Chen (Stochastic Environmental Research and Risk Assessment, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

A new C 19 -diterpenoid alkaloid in Aconitum georgei Comber - Lin-Lin Yao; Sheng-Qi Zhang; Ce Guo; Bin-Xian Li; Hua-Juan Yang; Tian-Peng Yin; Le Cai (Natural Product Research, 2024)

Fabrication and performance of novel multifunctional sodium alginate/polyvinylpyrrolidone hydrogels - Deli Lu; Chen Liu; Fengtian Zhu; Ying Liu; Yushi Lin; Qidong Yang; Sheng Han (Chemosphere, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Nitric oxide regulates the lignification and carotenoid biosynthesis of postharvest carrot (Daucus carota L.) - Miao Sun; Tao Yang; Xuan-Huan Qiao; Peng Zhao; Zhi-Peng Zhu; Guang-Long Wang; Lin-Lin Xu; Ai-Sheng Xiong (Postharvest Biology and Technology, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Dynamic response of root-associated fungal community structure to nitrogen and phosphorus additions in a subtropical forest - Shanshan Liu; Hao Yang; Luhong Zhou; Sheng-Sheng Jin; Lin Xie; Chengfang Lin; Ji-Zheng He; Yong Zheng (Pedobiologia, 2023)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Exploration of the downward transport mechanisms of biomass burning emissions from Indochina at the low boundary layer in East Asia - Chuan-Yao Lin; Wen-Mei Chen; Yang-Fan Sheng; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Environment, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Soil selenium enrichment in the Loess Plateau of China: Geogenic evidence, spatial distribution, and it's influence factors - Xuezhen Li; Qingye Hou; Yiren Duan; Yongchun Li; Kun Lin; Bo Li; Weikang Sheng; Yongliang Wang; Rilige Su; Zhoulei Gu; Tao Yu; Qifeng Tang; et al. (Chemosphere, 2023)

Emission-concerned coordinated dispatching of electrified autonomous mobility-on-demand system and power system incorporating heterogeneous spatiotemporal scales - Yujie Sheng; Yanxi Lin; Hongtai Zeng; Yang Yu; Qinglai Guo; Shiwei Xie (Sustainable Cities and Society, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Hydrogen sulfide delays postharvest ripening of white fleshed strawberry by regulating phytohormone accumulation and ROS generation - Miao Sun; Tao Yang; Xuan-Huan Qiao; Peng Zhao; Zhi-Peng Zhu; Kai-Yue Su; Chuan-Wen Sun; Zhao-Biao Xie; Shu-Song Zhang; Meng Xu; Lin-Lin Xu; Ai-Sheng Xiong (Postharvest Biology and Technology, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

Design of rich defects carbon coated MnFe2O4/LaMnO3/LaFeO3 heterostructure nanocomposites for broadband electromagnetic wave absorption - Xinyang Liu; Lin He; Guanghui Han; Jie Sheng; Yongsheng Yu; Weiwei Yang (Chemical Engineering Journal, 2023)

Hydroxylamine enhanced the degradation of diclofenac in Cu(II)/peracetic acid system: Formation and contributions of CH3C(O)O•, CH3C(O)OO•, Cu(III) and •OH - Jianying Wu; Jing Zou; Jinbin Lin; Sheng Li; Siying Chen; Xiaobin Liao; Jingxin Yang; Baoling Yuan; Jun Ma (Journal of Hazardous Materials, 2023)

Actionable insights into hazard mitigation of typical 3D printing waste via pyrolysis - Ziting Lin; Jingyong Liu; Haiming Cai; Fatih Evrendilek; Chuanghai Zhu; Fanjin Liang; Wenxiao Huang; Weixin Li; Chao He; Chunxiao Yang; Zuoyi Yang; Sheng Zhong; et al. (Journal of Hazardous Materials, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Development of a green fermentation strategy with resource cycle for the docosahexaenoic acid production by Schizochytrium sp. - Zi-Lei Chen; Lin-Hui Yang; Shao-Jie He; Yuan-Hang Du; Dong-Sheng Guo (Bioresource Technology, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Cofilin-1 induces acute kidney injury via the promotion of endoplasmic reticulum stress-mediated ferroptosis - Sihao Lin; Jie Wang; Bin Cao; Yang Huang; Xujun Sheng; Yingjian Zhu (Human Cell, 2023)
Ischemia–reperfusion injury (IRI) leads to acute kidney injury (AKI), which poses serious threat to public health and society. Many clinical studies were conducted to evaluate several biomarkers in AKI, among which Cofilin-1 remains to be a very promising one. To explore the potential mechanism of Cofilin-1 in AKI, we established an oxygen-glucose-deprivation (OGD)-induced AKI cell model. The overexpression and knock-down Cofilin-1 were used for gain- and loss-of-function. Pharmacological inhibitors were employed to study the related pathways. The results showed that Cofilin-1 was significantly upregulated in AKI cells, knocking down Cofilin-1 protected cells against the effect of OGD treatment and alleviated AKI phenotypes. Overexpression of Cofilin-1 might induce AKI by triggering ferroptosis, inhibiting NF-κB signaling or ER stress pathway attenuated Cofilin-1 induced lipid peroxidation and AKI. We also validated our findings in IRI-induced AKI mouse models in vivo. Our work elucidated that Cofilin-1 might induce AKI via promoting ER stress-mediated ferroptosis and argues it as a biomarker for early diagnosis of AKI. We also expect to offer novel insights on future therapeutic interventions.

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Distribution Characteristics and Influencing Factors of Bio-elements in the Human Hair of Uyghur Communities in an Oasis Area of Xinjiang, China - Muyesaier Tudi; Fengqing Jiang; Li Wang; Hairong Li; Shuangmei Tong; Jiangping Yu; Min Meng; Lin sheng Yang; Muhammad Ubaid Ali; Qiming Jimmy Yu; Huada Daniel Ruan (Biological Trace Element Research, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Ultraviolet-based synergistic processes for wastewater disinfection: A review - Yi-Xuan Zhang; Jue-Lin Xiang; Jun-Jie Wang; Hai-Sheng Du; Ting-Ting Wang; Zheng-Yang Huo; Wen-Long Wang; Min Liu; Ye Du (Journal of Hazardous Materials, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Consumer preferences for oyster trait attributes in China: A choice experiment - Bin Yuan; Yuhu Cui; Wei Liu; Wenqian Sheng; Hanxiao Xu; Lin Yang (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Duplicate genes as sources for rapid adaptive evolution of sperm under environmental pollution in tree sparrow - Shengnan Wang; Yingmei Zhang; Wenzhi Yang; Yue Shen; Zhaocun Lin; Sheng Zhang; Gang Song (Molecular Ecology, 2023)
Environmental pollution can result in poor sperm quality either directly or indirectly in birds. However, adaptive and compensatory sperm morphology changes and motility improvements have rapidly evolved in tree sparrows ( Passer montanus ) inhabiting polluted areas over the past 65 years. To identify the genetic underpinnings of the rapidly evolving sperm phenotype, we carried out population genomics and transcriptomics on tree sparrow populations in the two differently polluted places. We identified a gene encoding the serine/threonine protein kinase PIM1, which may drive rapid phenotypic evolution of sperm. An unprecedented and remarkable expansion of the PIM gene family, caused by tandem and segmental duplication of PIM1 , was subsequently observed in the tree sparrow genome. Most PIM1 duplicates showed a testis‐specific expression pattern, suggesting that their functions are related to male reproduction. Furthermore, the elevated expression level of PIM1 was consistent with our earlier findings of longer and faster swimming sperm in polluted sites, indicating an important role for duplicated PIM1 in facilitating the rapid evolution of sperm. Our results suggest that duplicated PIM1 provides sources of genetic variation that may enable the rapid evolution of sperm under environmental heavy metal pollution. The findings of this study indicated that duplicated genes can be targets of selection and predominant sources for rapid adaptation to environmental change and shed light on sperm evolution under pollution stress.

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

A comprehensive review on combustion, performance and emission aspects of higher alcohols and its additive effect on the diesel engine - Yanhui Zhang; Sheng Gao; Zhiqing Zhang; Weiqing Li; Tao Yuan; Dongli Tan; Lin Duan; Guanhua Yang (Fuel, 2023)

Non-targeted screening for contaminants derived from food contact water-borne coatings and risk assessment based on (Q)SAR matrix - Qing-Hua Yang; Qin-Bao Lin; Jia Liao; Hong-Sheng Ma; Xiao-Fen Wei; Yue Wang; Xiaowen Xu (Food Packaging and Shelf Life, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Ambient nitrogen dioxide and cardiovascular diseases in rural regions: a time-series analyses using data from the new rural cooperative medical scheme in Fuyang, East China - Teng-Fei Dong; Zhen-Qiu Zha; Liang Sun; Ling-Li Liu; Xing-Yang Li; Yuan Wang; Xiang-Long Meng; Huai-Biao Li; Hong-Li Wang; Huan-Huan Nie; Lin-Sheng Yang (Environmental Science and Pollution Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

A numerical investigation of the transport process of density currents over steep slopes and its implications for subsea cable breaks - Sheng-De Tsai; Jia-Lin Chen; Wen-Yang Hsu; Wei-Zhan Tsai; Andhy Romdani (Ocean Engineering, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

NRP1 contributes to stemness and potentiates radioresistance via WTAP-mediated m6A methylation of Bcl-2 mRNA in breast cancer - Yang Wang; Lin Zhang; Xiao-Lin Sun; Ya-Chun Lu; Si Chen; Dong-Sheng Pei; Lan-Sheng Zhang (Apoptosis, 2023)

Validation and accuracy analysis of wind products from scatterometer onboard the HY-2B satellite - Sheng Yang; Bo Mu; Haoqiang Shi; Chaofei Ma; Wu Zhou; Juhong Zou; Mingsen Lin (Acta Oceanologica Sinica, 2023)

Exploring consumer perception and acceptance of recycled merchandise under five-sense design - Jui-Che Tu; Cheng-Hsueh Yang; Sheng-Huei Lin; Kharisma Creativani (Environment, Development and Sustainability, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

A refined model of a typhoon near-surface wind field based on CFD - Youtian Yang; Lin Dong; Jiazi Li; Wenli Li; Dan Sheng; Hua Zhang (Natural Hazards, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Joint Model of Wind Speed and Corresponding Direction Based on Wind Rose for Wind Energy Exploitation - Zihao Yang; Yifan Lin; Sheng Dong (Journal of Ocean University of China, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Zkscan3 affects erythroblast development by regulating the transcriptional activity of GATA1 and KLF1 in mice - Zixuan Li; Binjie Sheng; Tingting Zhang; Tian Wang; Dan Chen; Gangli An; Xingbing Wang; Huimin Meng; Lin Yang (Journal of Molecular Histology, 2022)
ZKSCAN3 encodes a zinc-finger transcription factor that regulates the expression of important genes and plays a significant role in tumor development, pathogenesis, and metastasis. However, its biological functions under normal physiological conditions remain largely unknown. In our previous studies, using flow cytometry, we found that the deletion of Zkscan3 may cause abnormal erythropoiesis. In this study, we found that, in a Zkscan3 knockout mice model, the number of splenic early-stage (basophilic-erythroblasts) and late-stage (chromatophilic-erythroblasts to polychromatophilic-erythroblasts through orthochromatophilic-erythroblasts) erythroblasts increased, whereas the number of late erythroblasts in the bone marrow decreased. Moreover, the phenotype was exacerbated after treating mice with phenylhydrazine (PHZ), which causes severe hemolytic anemia. In the knockout mice treated with PHZ, the percentage of reticulocyte in the peripheral blood conspicuously increased, whereas MCHC and red blood cells decreased. Then, we performed RNA-seq and quantitative-polymerase chain reaction assay and found that the expression of GATA1 and Tiam1 in erythroblasts were upregulated, whereas KLF1 was downregulated. Luciferase assays showed that Zkscan3 inhibited the transcription of GATA1 and Tiam1 and promoted the expression of KLF1 . Additionally, ChIP and CO-IP results confirmed that Zkscan3 directly interacts with GATA1 and inhibits its transcriptional activity in MEL cells. Our results demonstrate, for the first time, the significant role of Zkscan3 in physiological erythropoiesis through the interaction with GATA1, both at the DNA and protein level, and with Tiam1 and KLF1 at the DNA level.

Cloning and expression analysis of hif-1α and downstream genes during hypoxic stress in cobia (Rachycentron canadum) - Jian-sheng Huang; Eric Amenyogbe; Lin-tong Yang; Zhong-liang Wang; Gang Chen; Wei-zheng Wang; Jian-dong Zhang (Aquaculture International, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Naringin Ameliorates Haloperidol-Induced Neurotoxicity and Orofacial Dyskinesia in a Rat Model of Human Tardive Dyskinesia - Mao-Hsien Wang; Chih-Chuan Yang; Hsiang-Chien Tseng; Chih-Hsiang Fang; Yi-Wen Lin; Hung-Sheng Soung (Neurotoxicity Research, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Ecological and health risk assessment of trace elements in surface soil in an arid region of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Binggan Wei; Li Wang; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Journal of Soils and Sediments, 2021)

Correction to: Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

An accounting of the external environmental costs of coal in Inner Mongolia using the pollution damage method - Hao-Dong Lv; Jin-Sheng Zhou; Lin Yang; Yi-Ming Li; Lu Liu (Environment, Development and Sustainability, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Estimation of monthly pan evaporation using support vector machine in Three Gorges Reservoir Area, China - Ji-Long Chen; Hong Yang; Ming-Quan Lv; Zuo-Lin Xiao; Sheng Jun Wu (Theoretical and Applied Climatology, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Difference of trace element exposed routes and their health risks between agriculture and pastoral areas in Bay County Xinjiang, China - Muyesaier Tudi; Dung Tri Phung; Huada Daniel Ruan; Lin-sheng Yang; Hai-Jun Guo; Des Connell; Ross Sadler; Cordia Chu (Environmental Science and Pollution Research, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Thermo-elastoplastic Model for Soft Rock Considering Effects of Structure and Overconsolidation - Yong-lin Xiong; Qi-lai Yang; Sheng Zhang; Guan-lin Ye; Gan-bin Liu; Rong-yue Zheng; Feng Zhang (Rock Mechanics and Rock Engineering, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

A new C -glycosyl flavone and a new neolignan glycoside from Passiflora edulis Sims peel - Yue Hu; Lin Jiao; Min-Hong Jiang; Sheng Yin; Pan Dong; Zhi-Min Zhao; De-Po Yang; Pei-Tsai Ho; Dong-Mei Wang (Natural Product Research, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Effect of clay content to the strength of gravel soil in the source region of debris flow - Ning-sheng Chen; Yan-chao Gao; Cheng-lin Yang; Gui-sheng Hu (Journal of Mountain Science, 2018)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Comparison of endosperm amyloplast development and degradation in waxy and non-waxy wheat - H. Yu; Y. Yang; X.Y. Chen; G.X. Lin; J.Y. Sheng; J.Y. Nie; Q.J. Wang; E.J. Zhang; X.R. Yu; Z. Wang; F. Xiong (Cereal Research Communications, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

Trichogramma parasitoids can distinguish between fertilized and unfertilized host eggs - Wen-Mei Du; Jing Xu; Yang-Yang Hou; Ying Lin; Lian-Sheng Zang; Xiangbing Yang; Jun-Jie Zhang; Chang-Chun Ruan; Nicolas Desneux (Journal of Pest Science, 2018)

Increased temperature mitigates the effects of ocean acidification on the calcification of juvenile Pocillopora damicornis, but at a cost - Lei Jiang; Fang Zhang; Ming-Lan Guo; Ya-Juan Guo; Yu-Yang Zhang; Guo-Wei Zhou; Lin Cai; Jian-Sheng Lian; Pei-Yuan Qian; Hui Huang (Coral Reefs, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Influence of Thread Design on Dental Implant Osseointegration Assayed Using the Lan-Yu Mini-Pig Model - Shih-Kang Chien; Shui-Sang Hsue; Chih-Shing Lin; Tzong-Fu Kuo; Duen-Jeng Wang; Jen-Chang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

Strength, Deformability and X-ray Micro-CT Observations of Deeply Buried Marble Under Different Confining Pressures - Sheng-Qi Yang; Yang Ju; Feng Gao; Yi-Lin Gui (Rock Mechanics and Rock Engineering, 2016)

Synthesis and evaluation as potential antitumor agents of novel ursolic acid derivatives - Ming-Chuan Liu; Sheng-Jie Yang; Lin-Hong Jin; De-Yu Hu; Wei Xue; Song Yang (Medicinal Chemistry Research, 2016)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

2,3,5-Trimethoxy-4-cresol, an anti-metastatic constituent from the solid-state cultured mycelium of Antrodia cinnamomea and its mechanism - Chin-Chung Lin; Ching-Chun Chen; Yueh-Hsiung Kuo; Jong-Tar Kuo; K. J. Senthil Kumar; Sheng-Yang Wang (Journal of Natural Medicines, 2015)

Altitudinal and latitudinal dependence of future warming in Taiwan simulated by WRF nested with ECHAM5/MPIOM - Chuan‐Yao Lin; Ying‐Jea Chua; Yang‐Fan Sheng; Huang‐Hsiung Hsu; Chao‐Tzuen Cheng; Yi‐Yin Lin (International Journal of Climatology, 2015)
It is difficult and inadequate to use a global model alone for projecting future climate changes in areas such as Taiwan, a complex geographic nature island, due to its coarse resolution. In this study, we have performed dynamic downscaling of Taiwan's climate in the recent past (1979–2003) and climate change projection for the near and distant future (2015–2039 and 2075–2099, respectively) by using the Weather Research Forecasting (WRF) model. The simulation is forced by the Max Plank Institute Hamburg, global model, ECHAM5/MPIOM. Simulation results showed close correlation between fine‐resolution downscaling by WRF nested with ECHAM5/MPIOM and the actual observation data for the period 1979–2003. Projection of future climate changes revealed both altitudinal and latitudinal variations in warming trend, with more significant temperature increase in mountain areas than in plain areas towards the end of the 21st century and more obvious warming in the north than in the south of Taiwan. The results obtained in this study can be applied to other regions of similar latitudes and with comparable relief.

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

Chryseobacterium profundimaris sp. nov., a new member of the family Flavobacteriaceae isolated from deep-sea sediment - Lin Xu; Ying-Yi Huo; Zheng-Yang Li; Chun-Sheng Wang; Aharon Oren; Xue-Wei Xu (Antonie van Leeuwenhoek, 2015)

Seismic response of embankment slopes with different reinforcing measures in shaking table tests - Yu-liang Lin; Wu-ming Leng; Guo-lin Yang; Liang Li; Jun-Sheng Yang (Natural Hazards, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Characteristics of Dew Formation and Distribution, and Its Contribution to the Surface Water Budget in a Semi-arid Region in China - Qiang Zhang; Sheng Wang; Fu-Lin Yang; Ping Yue; Tong Yao; Wen-Yu Wang (Boundary-Layer Meteorology, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

A new isobenzofuranone from the mangrove endophytic fungus Penicillium sp. (ZH58) - Jianxiang Yang; Riming Huang; Sheng Xiang Qiu; Zhigang She; Yongcheng Lin (Natural Product Research, 2013)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Monascusazaphilones A–C, three new azaphilone analogues isolated from the fungus Monascus purpureus BCRC 38108 - Ming-Der Wu; Ming-Jen Cheng; Yi-Jen Yech; Yen-Lin Chen; Kai-Ping Chen; Ping-Hsun Yang; Ih-Sheng Chen; Gwo-Fang Yuan (Natural Product Research, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Influence of gonadotropin-releasing hormone agonist on the effect of chemotherapy upon ovarian cancer and the prevention of chemotherapy-induced ovarian damage: an experimental study with nu/nu athymic mice - Qiong-yan Lin; Yi-feng Wang; Hui-nan Weng; Xiu-jie Sheng; Qing-ping Jiang; Zhi-ying Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Synthesis and Bioactive Studies of Complex 8-Hydroxyquinolinato-Bis-(Salicylato) Yttrium (III) - Xu Li; Qiang-Guo Li; Hui Zhang; Ji-Lin Hu; Fei-Hong Yao; De-Jun Yang; Sheng-Xiong Xiao; Li-Juan Ye; Yi Huang; Dong-Cai Guo (Biological Trace Element Research, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Electrostatic droplets assisted synthesis of alginate microcapsules - Keng-Shiang Huang; Chih-Hui Yang; Yung-Sheng Lin; Chih-Yu Wang; Kang Lu; Yu-Fan Chang; Yi-Ling Wang (Drug Delivery and Translational Research, 2011)

Delineation of the translocation of colicin E7 across the inner membrane of Escherichia coli - Yuh-Ren Chen; Tsung-Yeh Yang; Guang-Sheng Lei; Lung-JR Lin; Kin-Fu Chak (Archives of Microbiology, 2011)

Chemical-protein interactome and its application in off-target identification - Lun Yang; Ke-Jian Wang; Li-Shan Wang; Anil G. Jegga; Sheng-Ying Qin; Guang He; Jian Chen; Yue Xiao; Lin He (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Molecular characterization of a phenylalanine ammonia-lyase gene (BoPAL1) from Bambusa oldhamii - Lu-Sheng Hsieh; Yi-Lin Hsieh; Chuan-Shan Yeh; Chieh-Yang Cheng; Chien-Chih Yang; Ping-Du Lee (Molecular Biology Reports, 2011)

An alkali-tolerant xylanase produced by the newly isolated alkaliphilic Bacillus pumilus from paper mill effluent - Jing Wang; Wei-wei Zhang; Jin-ni Liu; Yao-ling Cao; Xiao-ting Bai; Yue-sheng Gong; Pei-lin Cen; Ming-ming Yang (Molecular Biology Reports, 2010)

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate - Sheng-Wei Feng; Yi-June Lo; Wei-Jen Chang; Che-Tong Lin; Sheng-Yang Lee; Yoshimitsu Abiko; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2010)

Molecular responses to the fungal pathogen Gibberella fujikuroi in the leaves of chewing cane (Saccharum officinarum L.) - Sheng Lin; Yifei Zhou; Guanshui Chen; Yang Zhang; Yanyun Zhang; Wenjun Ning; Daren Pan (Sugar Tech, 2010)

Construction of a Genetic Linkage Map and Mapping of a Female-Specific DNA Marker in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Xiaolin Liao; Hong-Yu Ma; Gen-Bo Xu; Chang-Wei Shao; Yong-Sheng Tian; Xiang-Shan Ji; Jing-Feng Yang; Song-Lin Chen (Marine Biotechnology, 2009)

Isolation and characterization of 30 novel polymorphic microsatellite loci from Japanese halfbeak, Hyporhamphus sajori (Temminck et Schlegel, 1846) - Shi-Chao Xing; Gen-Bo Xu; Guan-Pin Yang; Shan-Shan Liu; Xiao-Lin Liao; Yong-sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Artificial Gynogenesis and Sex Determination in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Yong-Sheng Tian; Jing-Feng Yang; Chang-Wei Shao; Xiang-Shan Ji; Jie-Ming Zhai; Xiao-Lin Liao; Zhi-Meng Zhuang; Peng-Zhi Su; Jian-Yong Xu; Zhen-Xia Sha; Peng-Fei Wu; et al. (Marine Biotechnology, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Active extracts of wild fruiting bodies of Antrodia camphorata (EEAC) induce leukemia HL 60 cells apoptosis partially through histone hypoacetylation and synergistically promote anticancer effect of trichostatin A - Mei-Chin Lu; Ying-Chi Du; Jiunn-Jye Chuu; Shiuh-Lin Hwang; Pao-Chuan Hsieh; Chih-Sheng Hung; Fang-Rong Chang; Yang-Chang Wu (Archives of Toxicology, 2009)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Timing of UHP metamorphism in the Hong’an area, western Dabie Mountains, China: evidence from zircon U–Pb age, trace element and Hf isotope composition - Yuan-Bao Wu; Shan Gao; Hong-Fei Zhang; Sai-Hong Yang; Wen-Fang Jiao; Yong-Sheng Liu; Hong-Lin Yuan (Contributions to Mineralogy and Petrology, 2007)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Effects of cardiotoxin III on expression of genes and proteins related to G2/M arrest and apoptosis in K562 cells - Sheng-Huei Yang; Chien-Hsun Tsai; Mei-Chin Lu; Yung-Ning Yang; Ching-Ming Chien; Sheng-Fung Lin; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Vibrational analysis of mandible trauma: experimental and numerical approaches - Shu-Li Lin; Sheng-Yang Lee; Long-Yi Lee; Wen-Ta Chiu; Che-Tong Lin; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2006)

Spatial-temporal changes and trends of ageing in China - Wu-yi Wang; Li Zhang; Hai-rong Li; Ri-bang Li; Lin-sheng Yang; Yong-feng Liao (Chinese Geographical Science, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)